Analysis of the Incidence of Ocular Extraintestinal Manifestations in Inflammatory Bowel Disease Patients: A Systematic Review - Bruno Songel-Sanchis; Jesús Cosín-Roger (Diagnostics)
Background: Inflammatory bowel disease (IBD), which includes Crohn’s disease and ulcerative colitis, primarily affects the gastrointestinal tract. Additionally, extraintestinal manifestations may occur in the liver, musculoskeletal system and eyes. Its etiology remains unknown, and further research is required in order to develop pharmacological drugs which achieve complete remission of the pathology. Objective: The aim of this study was to analyze the incidence of ocular extraintestinal manifestations in IBD patients. Methods: A total of six searches were carried out on the medical publication server “PubMed” in June and July 2024, using different keywords; a total of 323 results were obtained, of which 34 were finally selected for study. Results: Ocular extraintestinal manifestations in IBD patients are more common in the anterior pole of the eye, with uveitis, scleritis and episcleritis being the most usual ones. In the case of the posterior pole, the most common manifestations are posterior uveitis and optic neuritis. Conclusions: The incidence of ocular complications whose origin is inflammatory, such as uveitis, scleritis, episcleritis and neuritis, is higher than that of complications of non-inflammatory origin.